Value proposition analysis of innovative Finnish companies, specializing in Project Management Services : Blue Ocean and Ways to Success - Zhdanova, Yevgeniya (My University, 2021)
The value proposition is a fundamental component of the service-dominant logic that concentrates on value co-creation and resource integration. The service-dominant logic emphasizes that the customer determines the value. Thus, co-creation is a significant step to innovative value proposition and success achievement through beneficial interaction between firms and customers. The research aims to investigate value co-creation practices for crafting innovative value propositions in Finnish companies offering project management services, which may lead to value innovation. The investigation in this field is necessary to understand how project management companies operate, co-create value propositions, compete in red oceans or implement a blue ocean strategy. The study presents service-dominant logic, value co-creation, value innovation, blue ocean strategy, and market-shaping literature to explain how to introduce value innovation with customers instead of only for customers in the project management service industry. The thesis is qualitative research, and the chosen method is a multiple case study. The semi-structured interviews were conducted with five skilled and competent experts from different innovative Finnish companies working in the project management field to capture voices and compare experiences. The research provides a practical framework to contribute to a deeper understanding of the co-creation role in the value innovation process. Customers are vital resources for value proposition enhancement ideas in the service field. The results suggest that Finnish service companies specializing in project management services experiment, innovate in value through co-creation, and reshape markets. However, they are still far from creating fully-fledged blue oceans. The empirical research findings discover the best practices to value innovation: enhanced value proposition, digitalization (BIM, AI, and IoT), strategic partnerships and project alliances, and value co-creation: ecosystem and knowledge integration. The study also presents barriers to introducing innovative services and gaps in the project management industry in Finland. Future research possibilities could be detecting the gap in co-creation processes by analyzing the expected response from firms and actual response from customers about customers' expectations and needs. The research could be conducted further on how digitalization (AI, BIM, and IoT) reshapes the project management industry and, especially, firms’ value propositions.
Keywords: value creation; innovation (activity); customers; enterprises; project managers; project management; corporate strategies; development (active); success; analysis; service business; innovations; propositions; leadership (activity); fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development